Simultaneous Removal of Turbidity and Humic Acid Using Electrocoagulation/Flotation Process in Aqua Solution - Abdolmotaleb Seid-Mohammadi; Zahra Sharifi; Amir Shabanlo; Ghorban Asgari (Hamadan University of Medical Sciences, 2015)
In this study, the applicability of the Electrocoagulation/Flotation (ECF) process in batch operation was investigated for the simultaneous removal of turbidity and Humic acid (HA) using Fe and Al electrodes. The effects of solution pH (3 - 12), electrical potentials (10 - 30 V), initial turbidity concentration (300 - 1200 NTU), and reaction time (10 - 30 minutes) with or without HA were investigated in an attempt to achieve higher turbidity removal efficiency. The batch experimental results revealed that with initial turbidity of 300 NTU, at voltage of 30 V, after 30 minutes reaction times, and at pH values of 6 and 8, the ECF process for Fe and Al electrodes removed over 97% and 88% of turbidity, respectively. The percentage of turbidity removal from solution dropped with a decrease in voltages for both electrodes. The results displayed that the Fe-Fe electrode arrangement attained the highest performance for turbidity removal rate. As a result, ECF process was shown to be a very efficient, cost-effective, and promising process for efficient treatment of high turbid water. Regarding HA, the results showed that in ECF process over 67% and 43% of UV254 has been removed for Al and Fe electrodes, respectively at the optimum pH, 30 minutes reaction time and 30 V applied voltage. Thus, it can be considered that Fe and Al are the best electrodes for removing turbidity and HA, respectively.